Do football hooligans have human rights? - Marcheva, Deyana (Law Journal of New Bulgarian University, 2021)
Human rights are the â€œlast utopiaâ€ of our time that achieved contemporary prominence on the ruins of the last political utopias of twentieth century. All the international projects after World War 2 aspire to achieve a just balance between the basic individual rights and public interest. The human rights protection mechanisms introduce exceptions and qualifications to most of the human rights to allow for their restrictions proportional to the legitimate aims of the states. This article explores the human rights of the football hooligans starting with an analysis clarifying the historical, cultural and sociological aspects of the term â€œfootball hooliganâ€. Afterwards a detailed review of the case law of the European court of human rights is offered to reveal the status of the so called football hooligans as people whose basic rights could be restricted by the states upon wide discretion of the national authorities.